Environmental, social, and governance information disclosure and stock price crash risk: Evidence from Chinese listed companies - Xu, Nengrui; Liu, Jing; Dou, Huan (Frontiers in Psychology, 2022)
According to information asymmetry theory and stakeholder theory, this paper explores the impact and mechanism of ESG information disclosure on the company's future stock price crash risk basing on the A-share listed companies from 2010 to 2019. We find that ESG information disclosure significantly reduce the company's future stock price crash risk. This conclusion remains robust after a series of robustness tests such as PSM-DID. The heterogeneity analysis shows that the negative relationship between ESG disclosure and stock price crash risk is more significant in state-owned enterprises, companies with higher agency costs, and when companies in the bull market. The mechanism is that companies choose to disclose ESG information to alleviate information asymmetry problem and enhance corporate reputation capital, thus reduce the future stock price crash risk. This paper shows that strengthening ESG construction will help improve the efficiency of China's resource allocation and promote the capital market development.